Supervision Academic In The Independent Curriculum At Madrasah Ibtidaiyah Jambi City - Rapiko Rapiko; Umil Muhsinin; A A Musyaffa (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
The Madrasah Principal is the school personnel responsible for all activities at school. He has the authority and responsibility to Manages all educational activities in the school he leads. Supervision is a coaching activity planned to help teachers and staff other schools so they can do their jobs effectively. Objective This research is to find out the academic supervision strategies carried out by madrasa heads to improve teacher academic performance at Madrasah Ibtidaiyah (MI) in Jambi City.Results of academic supervision. . This research method is qualitative phenomenology with a study research design case. Data collection techniques through observation, interviews and documentation. Technique data analysis using flow, data reduction, presentation of data at the verification stage. Testing Data validity was carried out using a triangulation approach. The two teachers' planning stages were included in the good category with recap scores of 86% and 89%. In the implementation stage, class 1 teachers obtained a score of 86% in the good category, a score of 91% obtained by the class 4 teacher in the very good category. In the evaluation stage, both teachers were also included in the category both with recap scores of 86% and 85%. Meanwhile, the implementation of the Merdeka Curriculum at the SD/MI level prioritizes project-based learning in order to realize the Pancasila Student Profile. This is also very relevant to 21st century learning which equips students with the 4C skills needed to answer the challenges of the times. There are 3 (three) options in implementing or implementing the independent curriculum (IKM) at the SD/MI level, namely: Independent Learning Category, independent change category and independent sharing category at class I and class IV SD/MI levels starting in the 2022/2023 school year .